Shortfall of equipment for neonatal intensive care and the introduction of budget holding contracts. - Fenton, A C (1990)
As adequate allowance must be made for the costs of purchasing, maintaining, and updating equipment during the development of contracts the current standing of neonatal units with regard to available equipment was assessed. Data were collected as part of a one year prospective survey of the 17 perinatal units in the Trent region. Adequacy of provision of equipment for recognised intensive care cost was assessed using the recommendations of the British Paediatric Association and British Association of Perinatal Paediatrics. It was assumed that units without recognised intensive care cost had to be able to equip one cot to a standard of intensive care level 1 in the short term. Equipment more than 5 years old was considered likely to warrant replacement or major maintenance within the next two years. With these guidelines over 600,000 pounds would be required to provide sufficient equipment for all recognised level 1 intensive care cost and to allow units without funded cost to provide this level of care in the short term and to replace existing equipment more than 5 years old for these cost alone. This amount could be reduced by 25% by subdividing intensive care cost into levels 1 and 2, thereby reducing equipment requirements, but this would impair the units' ability to perform level 1 care at funded provision, which has already been shown to need expansion. Neither figure takes account of equipment requirements for infants requiring special care. In addition, no allowance has been made for purchase or update of ultrasound scanners or blood gas analysers. If the government's proposed reforms are to be implemented clinicians need to revise guidelines regarding essential equipment, and plans must be made to correct any existing shortfalls so that they do not become inherited financial liabilities for future budget holders.